اقبال اور لیوتار کے تصورِ مذہب کا تقابلی مطالعہA Comparative Study of Iqbal’s and Lyotard’s Concept of Religion (Al-Qamar, 2022)
Religion is not confined to a single department of human life. It’s a complete code of life. Iqbal believes that religion holds the central place in thoughts and deeds of a man. His works are greatly inspired from the basic sources of Islam. To him the love of the Holy Prophet (SAW) dominates and is reflected from the life of a true Muslim. For Iqbal, religion is a dynamic force, so he is a great critic of monasticism. He refutes the ontological theory of Plato. He considers that it has damaged the progressive thinking of a human mind by leading it to escapism. Christianity has suffered a lot by following the ideas of Plato. Islam is a religion of practical life and guides its followers in every walk of life. Lyotard following the western legacy of Philosophy does not approve any external source of knowledge. However, his works depict the concept of God. He rejects all the metanarratives, including religion. But his later works he reveal that to him the postmodernism and Christianity can make alliance in the end.
Keywords: Religion; Iqbal; Lyotard; Christianity; Islam; Postmodernism; Philosopy